The Temporal Paradox of Regions in the EU Seeking Independence: Contraction and Fragmentation versus Widening and Deepening?. Issue 5 (22nd May 2013) - Chamon, Merijn; Van der Loo, Guillaume
Abstract This article investigates the possibility of regional entities within EU Member States to become EU Member States in their own right following their secession from their mother state. International law does not automatically allow such regions to remain EU Member States since it refers this issue back to the constituent instruments of international organisations and a reading of both the EU Treaties and the ECJ's jurisprudence seems to preclude such a 'continued membership'. The article then further explores the legal issues which could arise during the accession process of the newly independent state. After suggesting solutions to bridge the gap between its secession and its own EU membership, it is argued that the key challenge for such a region would be to ensure a smooth transition, without the loss of prerogatives under EU law, from being an EU region to an EU Member State proper.